The Developmental Delay of Seedlings With Cotyledons Only Confers Stress Tolerance to Suaeda aralocaspica (Chenopodiaceae) by Unique Performance on Morphology, Physiology, and Gene Expression - Cao, Jing; Li, Xiaorong; Chen, Ling; He, Meixiang; Lan, Haiyan (Frontiers in Plant Science, 2022)
Cotyledons play an important role in seedling establishment, although they may just exist for a short time and become senescent upon the emergence of euphylla. So far, the detailed function of cotyledons has not been well understood. Suaeda aralocaspica is an annual halophyte distributed in cold deserts; its cotyledons could exist for a longer time, even last until maturity, and they must exert a unique function in seedling development. Therefore, in this study, we conducted a series of experiments to investigate the morphological and physiological performances of cotyledons under salt stress at different developmental stages. The results showed that the cotyledons kept growing slowly to maintain the normal physiological activities of seedlings by balancing phytohormone levels, accumulating osmoprotectants and antioxidants, and scavenging reactive oxygen species (ROS). Salt stress activated the expression of osmoprotectant-related genes and enhanced the accumulation of related primary metabolites. Furthermore, differentially expressed transcriptional profiles of the cotyledons were also analyzed by cDNA-AFLP to gain an understanding of cotyledons in response to development and salt stress, and the results revealed a progressive increase in the expression level of development-related genes, which accounted for a majority of the total tested TDFs. Meanwhile, key photosynthetic and important salt stress-related genes also actively responded. All these performances suggest that “big cotyledons” are experiencing a delayed but active developmental process, by which S. aralocaspica may survive the harsh condition of the seedling stage.